MOTIVATIONAL CONTENT ANALYSIS OF PRIMARY SCHOOL TEXTBOOKS ON LITERATURE IN CONTEXT OF D. MCCLELLAND’S THEORY - E. V. Bataeva (Образование и наука)
Introduction. The main motives of human behavior are formed at the primary school age. Several factors play a determining role in children’s development: up-bringing in the family, style of teaching at school, quality of popular literature and other sources of information, and, in particular, school textbooks. The special importance is given to the content quality of school textbooks. The influence of school textbooks is determined by the fact that school children should necessarily get familiar with the printed materials, resulting, as a consequence, in accepting the patterns of social interaction and motive-codes introduced there. Due to high constructivist potential of school textbooks, it seems necessary to carry out content analysis of textbooks’ for the purpose of identifying the influence on certain motive trends formation in schoolchildren.The aim of the publication is to present the methodology of motivational analysis of school textbooks on literature and the results of its approbation when studying the motivational content of Ukrainian textbooks for primary school.Methodology and research methods. The research methodology is based on comparative, socio-constructivist, sociocultural and system-activity approaches to implementation of educational process and preparation of didactic materials. Scientific methods involve: analysis and synthesis of the content of sociological, socio-psychological, pedagogical and methodical literature; content analysis of educational texts.Results and scientific novelty. The author’s methodology of motivational content analysis of primary school textbooks on literature developed in the context of D. McClelland’s theory is described. As the main categories of motivational content analysis of texts, the motives of behavior introduced by D. McClelland (achievements, affiliation, positive and negative power, avoidance of failure) as well as the motives of self-expression and refusal of affiliation have been used. As a result of the analysis of Ukrainian textbooks on literature for the 2nd–5th forms, it has been revealed that the affiliation motive occurred to be the dominant one, which has a positive motivational tendency. Among negative motivational tendencies have been discovered: low level of representation of motives of achievement and self-expression; a relatively high frequency of using negative motive of power (numerous examples of manipulating people for own self-affirmation, authoritarianism of literature characters, use weakness of subordinates, etc.) and the motive of failure avoidance (the person's inability/unwillingness to work hard self-removal under difficulties). It has been concluded that high level of negative motives in primary school textbooks could indirectly influence the formation of passive life attitudes of primary school children.Practical significance. The proposed author's methodology might be useful for the organization of comparative intercountry studies on identification of specific differences in training of children in different countries. The results of the research could also serve as one of the strongest justifications for the need to update and reform the system of elementary school education.